2018
DOI: 10.1177/1055665618813453
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Cephalometric Radiographs of Patients With Hemifacial Microsomia

Abstract: Objective: To clarify the morphological characteristics of hemifacial microsomia (HFM) by quantitative analysis of cephalometric radiographs. Design: Retrospective study of imaging data. Setting: Imaging data were obtained from the records of Sapporo Medical University Hospital. Patients: A total of 183 patients with HFM. Main Outcome Measures: We used linear and angular measurements and analyzed the middle face and lower face. Results: The ratios of the affected side to the unaffected (A/U) side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The findings of a significant reduction in body size on the affected side are generally consistent with the previous studies ( 6 8 , 10 ). We further found that the degree of asymmetry of the body was generally smaller than that of the ipsilateral ramus, and no significant shortening of the body was observed in infancy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings of a significant reduction in body size on the affected side are generally consistent with the previous studies ( 6 8 , 10 ). We further found that the degree of asymmetry of the body was generally smaller than that of the ipsilateral ramus, and no significant shortening of the body was observed in infancy.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, quantitative studies on the affected mandibular body in hemifacial microsomia are inconclusive (6)(7)(8)(9)(10)(11). Some studies considered it smaller than the contralateral side, causing clinical difference; while compensatory body growth was also found, with an incidence of up to 14.1% in the study population (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This difference was also seen comparing the affected to the unaffected side, and comparing patients that were severely and mildly affected (43). Another cephalometric study by Tokura et al showed that mandibular body hypoplasia on the affected side was unrelated to the severity of hypoplasia of the mandibular ramus and TMJ, and was stronger correlated to the degree of chin point deviation than the ramus hypoplasia in patients with CFM (44). Functional difficulties due to hypoplasia of the mandible and maxilla are common in patients with CFM and can have adverse impacts on breathing, feeding, speech and/or occlusion.…”
Section: Eyementioning
confidence: 93%
“…Their attempts to approach HFM with new measurement techniques have made progress on macroscopically understanding this disease. Tokura et al’s 8 evaluated multiple parameters of mandibular morphology based on HFM patients’ cephalometric radiographs; Elnaghy et al’s 9 found the difference between mandibular ramus bone mineral density on the affected and nonaffected side of HFM patients by cone beam computerized tomography assessments; Chen et al’s 10 investigated the cranial base involvements in HFM patients by 3-dimensional analysis, and Peng et al’s 11 characterized airway changes in HFM adolescents.…”
mentioning
confidence: 99%